Budgetary allocation: the clash of technique and politics (Revista da Faculdade de Direito, Universidade de São Paulo, 2023)
The main objective of this paper is to analyze the question of the legal contours of budgetary allocations, in the context of intense defense of a technobureaucratic allocation process that is intended to be impartial and impartial, and of severe criticism of political definitions. Arguments are presented to emphasize that, although quantifiable costs and benefits are fundamental for the allocative decision-making process, the choice of public expenditure takes place within the scope of selection between competing objectives and ends, being, fundamentally, political. Furthermore, it is intended to investigate the constitutional, legal and regimental requirements for the proposition of parliamentary amendments, comparing these minimum requirements with the recent Federal Supreme Court and the Federal Audit Court case laws. The most recent decisions by the TCU and the STF signal of the introduction of requirements not expressly provided for in the 1988 Political Charter, as well as in the legislation, with no trivial consequences for the allocation process within the National Congress. As research sources, in addition to the legislation that governs the proposal of parliamentary amendments, audit reports and TCU rulings that dealt with the subject are used, as well as STF decisions on parliamentary amendments, in addition to using research bibliographic and doctrinal basis for the reasoning of the arguments of this paper.